Alternanthera spp. based-phytoremediation for the removal of acetaminophen and methylparaben at mesocosm-scale constructed wetlands. Issue 11 (November 2021) - Mohammed, Ahmed A.; Mutar, Zahraa Hasan; Al-Baldawi, Israa Abdulwahab
Abstract: Recently, the spread of pharmaceuticals and personal care products (PPCPs) in the aquatic environment has steadily increased. In this study, phytoremediation technology, using an ornamental plant ( Alternanthera spp . ), was investigated to improve the removal of acetaminophen (AC) and methylparaben (MP) from a synthetically prepared wastewater. Three exposure lines (AC-line, MP-line and control-line) were performed with a total of 26 subsurface-horizontal constructed wetlands (SSH-CWs) that operated in batch feeding mode. The influence of plants in addition to the initial spiking concentration (20, 60 and 100 mg/L) of AC and MP on the removal efficiency was evaluated throughout the 35-days experiments. The highest removal efficiencies for AC and MP were 88.6% and 66.4%, respectively, achieved in the planted CWs; whereas only 29.7% and 21.9% were achieved in the control CWs for AC and MP, respectively. The results confirmed the role of Alternanthera spp . for accelerating the removal of AC and MP from synthetically contaminated wastewater in CWs. Abstract : Phytoremediation; Constructed wetlands; Phytotoxicity; Alternanthera spp; Pharmaceuticals and personal care products.